2014
DOI: 10.1088/1755-1315/20/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Application of support vector machine for classification of multispectral data

Abstract: Abstract. In this paper, support vector machine (SVM) is used to classify satellite remotely sensed multispectral data. The data are recorded from a Landsat-5 TM satellite with resolution of 30x30m. SVM finds the optimal separating hyperplane between classes by focusing on the training cases. The study area of Klang Valley has more than 10 land covers and classification using SVM has been done successfully without any pixel being unclassified. The training area is determined carefully by visual interpretation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 6 publications
1
29
0
1
Order By: Relevance
“…These results support previous studies that have demonstrated the potential of SVMs to identify different crop (Bahari, Ahmad, & Aboobaider, 2014;Devadas et al, 2012;Löw et al, 2013;Zheng et al, 2015). Sand dune classification accuracy decreased significantly over time.…”
Section: Resultssupporting
confidence: 91%
“…These results support previous studies that have demonstrated the potential of SVMs to identify different crop (Bahari, Ahmad, & Aboobaider, 2014;Devadas et al, 2012;Löw et al, 2013;Zheng et al, 2015). Sand dune classification accuracy decreased significantly over time.…”
Section: Resultssupporting
confidence: 91%
“…Fig. 4 explains the fundamental concept of support vector machine [4].Many techniques can be implemented to develop the classifier from binary to multiclass i.e. one against all and one against one [9].…”
Section: Svmmentioning
confidence: 99%
“…Parametric statistical learning techniques such as the maximum likelihood classifier (MLC) fail due to an inability to resolve the interclass confusion. This limitation can be overcome by applying a non-parametric classifier such as a support vector machine (SVM), which does not depend on any assumptions of the class distributions of data [41][42][43]. The SVM is an advanced machine learning algorithm, binary classifier, and a relatively new supervised classification technique [44].…”
Section: Introductionmentioning
confidence: 99%
“…The SVM is an advanced machine learning algorithm, binary classifier, and a relatively new supervised classification technique [44]. The SVM outperforms the other methods due to its robustness, high classification accuracy, and effective output results, even when using a small training sample [29,[41][42][43]. It operates on the principle of structural risk minimization (SRM) [45] and has overcome the problem of overfitting [41,44].…”
Section: Introductionmentioning
confidence: 99%